2020
DOI: 10.1108/sbm-12-2019-0119
|View full text |Cite
|
Sign up to set email alerts
|

Social impact of a participative small-scale sporting event

Abstract: PurposeTo examine the social impact of a small-scale sporting event and its influence on the willingness to support future events.Design/methodology/approachA self-supplied questionnaire was used with 248 residents-sportspeople that participated in the Valencia Triathlon. Descriptive analysis, exploratory and confirmatory factorials were done through SPSS, FACTOR and EQS.FindingsThree dimensions of positive impacts were identified; sporting participation and city image, social development and human capital and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
(87 reference statements)
0
17
0
2
Order By: Relevance
“…Research in the field of social sciences is represented by only 107 papers. Moreover, the topic of economics is covered by 9 articles, institutional -by 4 articles (Sowell, Mounts, 2005;Baumann et al, 2009;Sallent et al, 2011;Raya, 2012;Wicker et al, 2013;Saghiri, Wilding, 2013;Kim, 2013;Eren, 2017;Parra-Camacho et al, 2020;Phillips, Newland, 2014;Wagner, 2016;Pedras et al, 2020;Dori, Kemp, 2020). Only recent articles by Jane Hunt are focused specifically on history (Hunt, 2017;.…”
Section: Literature Review and Methodsmentioning
confidence: 99%
“…Research in the field of social sciences is represented by only 107 papers. Moreover, the topic of economics is covered by 9 articles, institutional -by 4 articles (Sowell, Mounts, 2005;Baumann et al, 2009;Sallent et al, 2011;Raya, 2012;Wicker et al, 2013;Saghiri, Wilding, 2013;Kim, 2013;Eren, 2017;Parra-Camacho et al, 2020;Phillips, Newland, 2014;Wagner, 2016;Pedras et al, 2020;Dori, Kemp, 2020). Only recent articles by Jane Hunt are focused specifically on history (Hunt, 2017;.…”
Section: Literature Review and Methodsmentioning
confidence: 99%
“…Other types of social impact research investigate the influence of social impact on residents' intentions (e.g., Kaplanidou et al, 2013 ; Prayag et al, 2013 ; Inoue and Havard, 2014 ). Several types of intentions have been utilized in research streams, such as positive word of mouth (Inoue and Havard, 2014 ), event support (Kaplanidou et al, 2013 ; Prayag et al, 2013 ; Parra-Camacho et al, 2020b ), support for sports policy (Parra-Camacho et al, 2020d ), and future intention to host the event (Liu, 2016 ; Oshimi et al, 2016 ; Parra-Camacho et al, 2020a ). However, little evidence exists on the relationships between social impact and actual residents' behavior (i.e., viewing behavior).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies that focused on non-mega-sporting events perceived increased social benefits in recent years. For example, Parra-Camacho et al (2020) focused on residents who participated in a triathlon in Valencia, Spain, and explored three social impacts: social development and human capital, sport participation and city image, and economic development. Another study that conducted a questionnaire survey with spectators of Wuhan Marathon in China revealed that, social impacts had a significant positive impact on the quality of life and event support (Duan et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study that conducted a questionnaire survey with spectators of Wuhan Marathon in China revealed that, social impacts had a significant positive impact on the quality of life and event support (Duan et al , 2020). Further, prior research discussed that social development and human capital allow residents to have a sense of well-being and have the opportunity to relate to new people as well as include disadvantaged groups and those at risk of social exclusion (Parra-Camacho et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%